CHEMICAL STATE OF POLAR STRATOSPHERIC AEROSOLS - イワサカ, ヤスノブ; ハヤシ, マサヒコ; コンドウ, ユタカ; コイケ, マコト; コガ, セイジ; ヤマトウ, マサヒコ; /; IWASAKA, Yasunobu; HAYASHI, Masahiko; KONDO, Yutaka; KOIKE, Makoto; KOGA, Seiji; et al. (National Institute of Polar Research, 1992)
P(論文) Electron microscopic observation of individual particles collected in the winter Arctic stratosphere with a balloon-borne impactor showed the possibility that particles containing nitric acid were formed above the background sulfate particle layer during the cold winter season. External mixing of nitric acid and sulfate particles was observed in the region of 18.8-19.6km (the upper part of the sulfate particle layer) during the measurements of January 31,1990. One possible explanation of this phenomenon is sedimentation of nitric acid particle, which has been speculated as an important process causing denitrification of the polar stratosphere and polar ozone depletion. departmental bulletin paper